Factors associated with nurses' self-efficacy in oral care at Oulu University Hospital, Finland - Roosa-Maria Kivilahti; Tiia Ahomäki-Hietala; Hannu Vähänikkilä; Taru Aro; Vuokko Anttonen; Marja-Liisa Laitala; Anna-Maija Syrjälä (Medical Journals Sweden, 2024)
Objectives: This study aimed to investigate factors associated with nurses' self-efficacy in oral care among infection-sensitive patients in a university hospital. Material and methods: All the nurses working in five wards of internal medicine and one department of oncology at Oulu University Hospital, Finland (n = 114) were recruited. Data were collected with a questionnaire containing 10 self-efficacy items (scored 0 to 10) and nine knowledge items (five-point Likert scale) that were validated in an earlier pilot study. Factor analysis was performed for the self-efficacy scale and a mean score was calculated for the knowledge scale. A multivariate linear regression model was used to analyze the association between explanatory variables and self-efficacy factor scores. Results: Factor analysis revealed self-efficacy factors: Practical skills, Self-confidence in taking care of patients' oral hygiene, and Confidence in detecting oral problems (factor scores varied between 4.9 and 8.8). A higher mean score for the knowledge scale was positively associated with the factor Practical skills (B = 0.5, p < 0.05). Longer working experience was associated with higher factor scores in Self-confidence in taking care of patients` oral hygiene and Confidence in detecting oral problems. Conclusions: Better oral health-related knowledge and longer working experience were positively associated with oral health-related self-efficacy.